Monitoring real time polymorphic transformation of sulfanilamide by diffuse reflectance visible spectroscopy - Tracy O. Ehiwe; Bruce D. Alexander; John C. Mitchell; Martin J. Snowden; Laura J. Waters (Elsevier, 2016)
This study investigated the development of a novel approach to surface characterization of drug polymorphism and the extension of the capabilities of this method to perform 'real time' in situ measurements. This was achieved using diffuse reflectance visible (DRV) spectroscopy and dye deposition, using the pH sensitive dye, thymol blue (TB). Two polymorphs, SFN-β and SFN-γ, of the drug substance sulfanilamide (SFN) were examined. The interaction of adsorbed dye with polymorphs showed different behavior, and thus reported different DRV spectra. Consideration of the acid/base properties of the morphological forms of the drug molecule provided a rationalization of the mechanism of differential coloration by indicator dyes. The kinetics of the polymorphic transformation of SFN polymorphs was monitored using treatment with TB dye and DRV spectroscopy. The thermally-induced transformation fitted a first-order solid-state kinetic model (R2=0.992), giving a rate constant of 2.43×10−2 s−1.